Psychological background of the internal picture of illness in patients with multiple sclerosis - Simonenko Григорій (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to the psychological background of the internal picture of illness in patients with multiple sclerosis. This internal picture is based on numerous psychological indicators, balance of interaction of conscious and unconscious processes. Unconscious processes are often understood as mechanisms of protection that influence on the adaptive capacity of patients. An internal picture of illness in patients with multiple sclerosis is formed by cognitive, mnemonic and emotional disorders. In this case, general fatigability, depressive and anxiety disorders, reduction of short-term memory are dominated, while fear is not characteristic. Maladaptive type of relation to the disease is dominated, this correlates with the magnitude and number of focuses of demyelination in the brain.